PENGARUH PERBEDAAN PENERAPAN METODE INKORPORASI BAHAN AKTIF TERHADAP STABILITAS DAN EFEKTIVITAS FILM ANTIMIKROBA - Reskiati Wiradhika Anwar (Universitas Darussalam Gontor, 2019)
The incorporation method is the selection of techniques used in combining active ingredients with the components of the film matrix. In the incorporation process the mixing that occurs causes an interaction between the film matrix and the active ingredient. The addition of antimicrobial compounds that aim to inhibit the growth of microorganisms will also affect the application of its function. Knowing the effect of different incorporation methods on the stability and effectiveness of antimicrobial functions is the goal of this study. The incorporation methods used are direct mixing, coating and encapsulation mixing. The active ingredients used are capsicum and packaging matrix composed of agar, tapioca and glycerol. The stability of the incorporated active ingredient is measured by looking at the resulting inhibition index and predicting the longest shelf-life by applying the encapsulation mixing method for up to 21 days. The effectiveness of the antimicrobial film function was tested by applying it as a packaging for fresh chicken meat with the lowest E.coli growth rate on the antimicrobial film coating method.